PENINGKATAN AKUNTABILITAS BUMDESA SUKAMANDI DAN MEMPAYA BELITUNG TIMUR - Yasni, Raynal (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
The program for preparing financial reports for Village Owned Enterprise (VoE) Sukamandi and Mempaya in East Belitung Regency in 2023 is a continuation of the 2022 community service program for Sukamandi Village and the first program in Mempaya Village using Excel application. The activities include training, visitation, consultation, and mentoring to prepare more VoE financial reports following standards, as well as to strengthen the human resource capacity of village officials whose role is to assist VoE in preparing financial reports using the automated Excel application. Advanced VoE Accounting Training was conducted offline for 2 days, and offline and online assistance for VoEs selected by the Social, Community, and Village Empowerment Office of East Belitung Regency was also achieved very well. The community service activity output target is a standardized financial report on VoE Sukamandi East Belitung that is meant to make VoE a more transparent and accountable entity. For VoE Mempaya, this activity initiated the preparation of financial reports in the development of its established business.